Understanding "The Athletic Labour of Femininity" Through the Experiences of Turkish Female Personal Trainers - Berna Can; Tayfun Şirin; Yeliz Eratlı Şirin; İrem Kavasoğlu (Pamukkale University, 2024)
The momentum of social media in the world of sports has created a wide range of opportunities for women in sports. One of the most obvious of these opportunities is undoubtedly related to economic visibility. The current research aims to examine how female trainers in the health and fitness sector, who actively participate in the creation and consumption of sports, represent themselves on Instagram through the concept of the athletic labour of femininity in the light of Turkey's gender regime and neoliberal feminism. In this study, which applied quantitative content analysis to a total of 1100 photographs of eleven individual coaches (11), eight in-depth individual interviews were conducted, and these qualitative data were analyzed by thematic analysis method. The quantitative and qualitative findings of the research show that women trainers in the health and fitness sector construct coaching that is in line with neoliberal femininity. On the other hand, power relations based on Turkey's neoconservative, religious patriarchal norms influence the market-based decisions trainers make about their sharing. As a result, Turkey-specific dynamics are at the forefront of trainers' athletic endeavours, which they focus on building a brand image. This study offers a perspective on how personal trainers serving in the healthy living and fitness industry use Instagram as a marketing tool, what economic opportunities they get, and what they negotiate while improving their visibility on Instagram, in the context of neoliberal femininity and Turkey's gender regime.